2021
DOI: 10.1038/s41598-021-81576-y
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of early failure rate and its risk factor with 2157 total ankle replacements

Abstract: The failure rate of TAA is still higher than that of other joint replacement procedures. This study aimed to calculate the early failure rate and identify associated patient factors. Data from the Korean Health Insurance Review and Assessment Service database from 2009 to 2017 were collected. We evaluated patients who had TAA as a primary surgical procedure. Early failure was defined as conversion to revision TAA or arthrodesis after primary TAA within five years. Patients with early failure after primary TAA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…6 More recent studies of 5-year TAR outcomes have reported reoperation rates ranging from 9.1% to 23%. 15,18,[30][31][32] Taken together, data from the current study suggest improved TAR survival to revision and explant surgery in recent years. This finding further supports improved outcomes following TAR as a driver of minimal increases in annual TAR revisions with respect to the rapidly increasing number of TAR procedures performed each year.…”
Section: Discussionmentioning
confidence: 72%
“…6 More recent studies of 5-year TAR outcomes have reported reoperation rates ranging from 9.1% to 23%. 15,18,[30][31][32] Taken together, data from the current study suggest improved TAR survival to revision and explant surgery in recent years. This finding further supports improved outcomes following TAR as a driver of minimal increases in annual TAR revisions with respect to the rapidly increasing number of TAR procedures performed each year.…”
Section: Discussionmentioning
confidence: 72%
“… 22 A more recent national (Republic of Korea) database review of 2157 primary TAA also revealed diabetes mellitus, along with chronic pulmonary disease, to be associated with early failure in TAA. 17 In contrast, patients with diabetes and ankle arthritis who underwent TAA at a single institution had similar clinical outcomes compared with their nondiabetic counterparts. 14 Although patients with diabetes had increased body mass index, and worse ASA preoperative grades, they did not have a significantly different complication or infection rate.…”
Section: Discussionmentioning
confidence: 95%
“…12,21,54 However, the role of excess weight or obesity as a prognostic factor for TAA is still under debate. 20,31,33,37…”
Section: Introductionmentioning
confidence: 99%
“…12,21,54 However, the role of excess weight or obesity as a prognostic factor for TAA is still under debate. 20,31,33,37 In orthopaedic clinical practice, body weight is a crucial criterion in patient selection since the negative effect of higher body mass index (BMI) on hip and knee arthroplasty outcomes is proven. 27,41,42 Furthermore, the arterial collateral capacity and the soft tissue coverage decrease toward the end of the lower limb.…”
Section: Introductionmentioning
confidence: 99%